Brill's companion to the reception of Aristophanes - Walsh, Philip, 1977- (Brill's companions to classical reception, 2016)
"Brill's Companion to the Reception of Aristophanes provides a substantive account of the reception of Aristophanes (c. 446-386 BC) from Antiquity to the present. Aristophanes was the renowned master of Old Attic Comedy, a dramatic genre defined by its topical satire, high poetry, frank speech, and obscenity. Since their initial production in classical Athens, his comedies have fascinated, inspired, and repelled critics, readers, translators, and performers. The book includes seventeen chapters that explore the ways in which the plays of Aristophanes have been understood, appropriated, adapted, translated, taught, and staged. Careful attention has been given to critical moments of reception across temporal, linguistic, cultural, and national boundaries. Contributors are Gregory Baker, Cécile Dudouyt, John Given, Matthew J. Kinservik, Stavroula Kiritsi, David Konstan, Mike Lippman, C.W. Marshall, Alexandre G. Mitchell, Mark Payne, Charles Platter, James Robson, Ralph Rosen, Niall W. Slater, Gonda Van Steen, Philip Walsh, Rosie Wyles, and Donna Zuckerberg."--